2014
DOI: 10.1016/j.still.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Long term changes in soil properties and enzyme activities after almond shell mulching in avocado organic production

Abstract: The recycling of almond shell as mulch would allow avocado orchards to be managed organically, maintaining plant yield and improving soil conditions simultaneously. This study aims to analyze the long term effects of successive applications of almond shell as mulching for organically grown avocado. Effects on soil properties, enzyme activities and soil carbon storage as well as avocado yield and growth were studied in comparison to no-tillage conventionally managed (using mineral fertilizers and herbicides) av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 34 publications
(43 reference statements)
3
26
1
Order By: Relevance
“…Catalase activity had no significant correlations with any tested soil nutrients except for EK (Table 5). Increased soil enzyme activities might be due to increased SOC and C and N immobilization during straw decomposition after application, as several studies have shown that soil enzyme activities can be affected by SOC [53][54][55]. Soil pH did not show significant effects on soil enzymes, except for alkaline phosphatase, in this study.…”
Section: Discussioncontrasting
confidence: 42%
“…Catalase activity had no significant correlations with any tested soil nutrients except for EK (Table 5). Increased soil enzyme activities might be due to increased SOC and C and N immobilization during straw decomposition after application, as several studies have shown that soil enzyme activities can be affected by SOC [53][54][55]. Soil pH did not show significant effects on soil enzymes, except for alkaline phosphatase, in this study.…”
Section: Discussioncontrasting
confidence: 42%
“…In addition to macroaggregates formation, organic matter can also stabilize and increase the size of soil aggregates (Chenu et al ., ). On the other hand, unlike synthetic mulches, that need to be removed after a period of time, organic mulches decompose and they need to be re‐applied, increasing water holding capacity, releasing nutrients and promoting favourable soil biotic activities, such as soil respiration and microbial biomass (López et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Mulching techniques have emerged in recent years to address these soil constraints yielding positive results in a variety of scenarios. An early study by Kumar et al (1985) and other more recent studies (Kar & Kumar, 2007;Mubarak et al, 2009;Okonkwo et al, 2011;García-Moreno, 2013;López et al, 2014;Zribi et al, 2015) reported the positive effects of mulches and organic amendments on soil physical properties, such as increased water retention and decreased soil evaporation.…”
Section: Measurementsmentioning
confidence: 96%